Spatiotemporal variation of terrestrial carbon sequestration in tropical urban area (case study in Surakarta District, Indonesia) - Danardono, Danardono; Sunariya, M. Iqbal Taufiqurrahman; Fikriyah, Vidya Nahdiyatul; Cholil, Munawar (Quaestiones Geographicae, 2021)
The value of terrestrial carbon sequestration in urban areas, due to lack of vegetation as a carbon sink, is rarely studied. In fact, urban areas have high carbon emission values, which must be minimised. On the other hand, the value of carbon sequestration in urban areas is very dynamic due to natural factors from the environment and non-natural factors from anthropogenic activities. The main objectives of this study are to identify the carbon dioxide sequestration in urban areas, especially in tropical climates, and to determine the dynamics of carbon sequestration in urban areas for a year. The results show that carbon sequestration in tropical urban areas has a significant value compared with urban areas in temperate climates. This condition happens because there are still green open spaces in gardens and agricultural lands. The value of carbon sequestration in this tropical urban area experiences monthly dynamics caused by rainfall variation and anthropogenic activities, such as land conversion and plant type conversion in agricultural lands.